2020
DOI: 10.1186/s40798-020-00245-y
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Physical Fitness Qualities and Sport-Specific Technical Skills in Female, Team-Based Ball Players: A Systematic Review

Abstract: Background: Understanding the relationships between physical fitness attributes and sport-specific technical skills may assist with the establishment of beneficial training interventions. The aim of this systematic review was to determine if physical fitness qualities were associated with performance of sport-specific technical skills in female, team-based ball players. Methods: Five databases (MEDLINE, EMBASE, SPORTDiscus, ProQuest, and Scopus) were searched for relevant studies up to April 15, 2019. Full-tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 85 publications
1
38
0
Order By: Relevance
“…Till et al [ 37 ] conducted a retrospective study in which it was shown that United Kingdom Academy players with lower skinfolds showed long-term progression in their professional sports careers. As a result, evaluating body fat could be the best way to monitor individual changes in diet and/or personalized training as well as other changes [ 38 , 39 ]. In the rugby union case, anthropometric determinations could also be used as a valuable tool for coaches when assessing the profile or position in the game for each player.…”
Section: Discussionmentioning
confidence: 99%
“…Till et al [ 37 ] conducted a retrospective study in which it was shown that United Kingdom Academy players with lower skinfolds showed long-term progression in their professional sports careers. As a result, evaluating body fat could be the best way to monitor individual changes in diet and/or personalized training as well as other changes [ 38 , 39 ]. In the rugby union case, anthropometric determinations could also be used as a valuable tool for coaches when assessing the profile or position in the game for each player.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to account for the various types of study analysed (randomized and nonrandomized studies, including case series), 3 out of 34 items were phrased in two different forms. The quality of the studies was established as follows: poor ≤ 14; fair 15-19 and good ≥ 20 [57].…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Anthropometric parameters and motor tests results are decisive factors for the selection of youth national female volleyball teams [ 34 ]. However, a small number of works assess the relationship between motor performance and the effectiveness of technical elements in volleyball [ 35 – 38 ]. Katić et al [ 35 ] proved that the mechanisms regulating the force influence the performance of attack, block, and play, while the processes responsible for speed and power have a greater influence on the effectiveness of serve reception.…”
Section: Discussionmentioning
confidence: 99%